The Role of The Sharia Supervisory Board in Risk Mitigation in Islamic Financial Institutions - Hendra, Joni; Ghafar, Abd; Cahnawawi, Safuan Tri; Sholatullah, Sholatullah (CV. Rayyan Dwi Bharata, 2025)
The Sharia Supervisory Board (SSB) plays a critical role in ensuring the compliance of Islamic financial institutions with Sharia principles. Beyond its function as a compliance authority, the SSB also contributes significantly to risk mitigation within Islamic financial institutions. This study explores the strategic role of the SSB in identifying, assessing, and minimizing Sharia-related and operational risks. The presence of the SSB ensures that all financial products, services, and operations adhere strictly to Islamic law, thereby preventing reputational and legal risks. Additionally, the SSB’s involvement in governance, product structuring, and continuous auditing enhances transparency and promotes stakeholder trust. The findings highlight that an active and competent Sharia Supervisory Board not only strengthens the ethical foundation of Islamic finance but also enhances overall risk management and organizational resilience.